Digital Marketing Strategy with Impact of Delivery Time on Customer Satisfaction in Online Food Delivery - Lely Wijayanti (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study examines the interplay between physical distribution speed and digital promotional vectors in shaping customer satisfaction within app-based food delivery ecosystems. Utilizing objective transaction-level data comprising 4093 fully delivered orders from the Zomato platform, an ordinary least squares regression framework was operationalized to evaluate direct and moderating structural pathways. The empirical findings reveal that delivery time does not exert a statistically significant direct impact on numeric customer ratings, suggesting a paradigm shift from raw logistics speed toward holistic experiential value. Conversely, free delivery incentives significantly enhance customer satisfaction, while promotional discount codes operate as critical psychological buffers that expand consumer tolerance thresholds during operational logistics delays. Although the baseline predictive model exhibits low explanatory power, confirming that satisfaction is a complex multidimensional construct, strict variance diagnostics validate structural parameter stability. These insights offer actionable strategic directives for platform managers, emphasizing the transition toward automated data-driven service recovery tools and targeted pricing interventions to stabilize consumer retention in highly competitive digital application markets.